Evaluation of beam hardening artifacts around dental implants: CT study on bovine ribs - Serindere Gozde; Aktuna Belgin Ceren; Serindere Mehmet; Berkay Belgin Huseyin; Orhan Kaan (Balkan Stomatological Society, 2023)
Background/Aim: The aim of this study was to evaluate beam hardening artifacts generated by Grade 4 and Grade 5 dental implants on computed tomography (CT) images at low and high kilovoltage peaks (kVp). Material and Methods: A total of 16 implants, 8 of which were Grade 4 and 8 were Grade 5, were inserted into bovine ribs. CT images of bovine ribs were acquired using two different exposure protocol: low kVp and high kVp. Beam hardening artifacts generated by Grade 4 and Grade 5 dental implants were calculated by the mean Hounsfield unit (HU) within a standardized region-of-interest (ROI). Results: Artifact in Grade 4 implants were greater than that in Grade 5 implants. Also, artifacts at the high kVp were lower than that at the low kVp. Conclusions: CT scans providing HU values can be used to evaluate the beam hardening artifact. Beam hardening artifacts decreased in the CT images with high kVp. Grade 5 dental implants have an advantage by producing less severe beam hardening artifacts.